Anisakiasis Annual Incidence and Causative Species, Japan, 2018–2019 - Sugiyama, Hiromu; Shiroyama, Mitsuko; Yamamoto, Ikuyo; Ishikawa, Takashi; Morishima, Yasuyuki (Emerging infectious diseases, 2022)
Using data from 2018–2019 health insurance claims, we estimated the average annual incidence of anisakiasis in Japan to be 19,737 cases. Molecular identification of larvae revealed that most (88.4%) patients were infected with the species Anisakis simplex sensu stricto. Further insights into the pathogenesis of various anisakiasis forms are needed.